Imaging Evaluation of Thymoma and Thymic Carcinoma - Strange, Chad D.; Ahuja, Jitesh; Shroff, Girish S.; Truong, Mylene T.; Marom, Edith M. (Frontiers in Oncology, 2022)
Imaging is integral in the management of patients with thymoma and thymic carcinoma. At initial diagnosis and staging, imaging provides the clinical extent of local invasion as well as distant metastases to stratify patients for therapy and to determine prognosis. Following various modalities of therapy, imaging serves to assess treatment response and detect recurrent disease. While imaging findings overlap, a variety of CT, MRI, and PET/CT characteristics can help differentiate thymoma and thymic carcinoma, with new CT and MRI techniques currently under evaluation showing potential.